(untitled) (CIPEEX, 2025)
The article highlights the growing elderly population in Brazil and the challenges associated with aging, such as sarcopenia and falls, which are significant concerns due to their serious consequences, including fractures, functional decline, and risk of institutionalization. The objective of the study is to identify the history of falls, body composition, and muscle strength of the participants. This is a cross-sectional and descriptive study involving 120 elderly participants in the Open University for the Elderly Project – UniAPI, at UniEVANGÉLICA, Anápolis-GO. The sample was predominantly female (91.7%) with a mean age of 71.1 years. Participants answered questionnaires about falls and underwent physical examinations to assess Body Mass Index (BMI), handgrip strength, and performance on the sit-to-stand test. The results showed that 40% of the elderly reported falls in the last 12 months. BMI analysis revealed that 18.3% were underweight, 45% were eutrophic (normal weight), 12.5% were overweight, and 24.2% were obese. Handgrip strength was reduced in 54.2% of participants, and 52.5% performed poorly on the sit-to-stand test. Among the 48 elderly individuals who fell, 45.8% had a normal BMI, 50% had reduced handgrip strength, and 52.1% performed poorly on the sit-to-stand test. Therefore, the high prevalence of muscle strength and endurance deficiencies is highlighted, reinforcing the need for interventions to prevent falls and improve the quality of life of older adults.